Potential biomarkers in patients with systemic sclerosis. (11th October 2017) - Delle Sedie, Andrea; Riente, Lucrezia; Maggiorini, Lavinia; Pratesi, Federico; Tavoni, Antonio; Migliorini, Paola; Puxeddu, Ilaria
Abstract: Aim: Reduced capillary density is considered the hallmark of systemic sclerosis (SSc) leads to tissue hypoxia, a condition that usually induces angiogenesis. The objective of our study is to investigate mediators regulating angiogenesis in SSc and to correlate their levels with serological and clinical parameters. Methods: vascular endothelial growth factor, fibroblast growth factor‐2, endostatin, thrombospondin‐1 and soluble vascular cell and intracellular adhesion molecules (sICAM‐1 and sVCAM‐1) were measured in sera of SSc and normal subjects by enzyme‐linked immunosorbent assay. Results: Among the pro‐ and anti‐angiogenic mediators, endostatin was significantly higher in SSc than in the control subjects. Out of the proteases involved in endostatin production, elastase but not cathepsin‐L, was significantly increased in SSc patients. The soluble adhesion molecules sICAM‐1 and sVCAM‐1 were significantly increased and they occur in parallel. sICAM‐1, but not sVCAM‐1 positively correlates with the inflammatory markers C‐reactive protein (CRP) and erythrocyte sedimentation rate (ESR). Conclusions: Endostatin, elastase and the soluble adhesion molecules (sICAM‐1 and sVCAM‐1) are potentially involved in the pathogenesis of SSc. Moreover, the significant correlation observed between sICAM‐1 and CRP and ESR indicates that sICAM‐1 might be a useful biomarker of the inflammatory state of the disease.